Arsenic-bridged magnetic interactions in an emerging two-dimensional FeAs nanostructure on MnAs - Helman, Christian; Ferrari, Valeria Paola; Llois, Ana Maria (American Physical Society, 2015)
Fil: Helman, Christian. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina